Comparative analysis of Abnormal Return and Trading Volume Activity Before and After the Announcement of the Covid 19 Pandemic-In financial companies listed on the Indonesia Stock Exchange (IDX) - Marsuni, Nur Sandi; D'Ornay, Anastasia; Nersiyanti, Nersiyanti; Habbe, Hamid; Nagu, Nadhirah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to analyze the reaction of the Indonesian capital market to the first case of Covid-19 by using Abnormal Return (AR), and Trading Volume Activity (TVA) before and after the Covid announcement period in Indonesia. Observations began seven days before and seven days after the event. The population for this study uses financial sector data registered in February and March 2020 on the IDX. The sampling technique used was purposive sampling with a total of 30 financial companies that met the criteria. This study uses quantitative research and comparative research testing methods with the Wilcoxon Signes Rank Test. The results of this study show significant differences in AR before and after the announcement of the Covid-19 pandemic, where these differences are indicated by an increase in Abnormal Returns after the announcement, investors trust companies more before the announcement which already provides returns or profits rather than having to predict profits. what you get in the future. The results of the wilxocon signed rank test showed that there was a significant difference in Trading Volume Activity before and after the announcement of covid .